High-dose pyridoxine treatment for inherited glycosylphosphatidylinositol deficiency - Tanigawa, Junpei; Nabatame, Shin; Tominaga, Koji; Nishimura, Yoko; Maegaki, Yoshihiro; Kinosita, Taroh; Murakami, Yoshiko; Ozono, Keiichi (Brain & development (Tokyo. 1979), 2021)
We aimed to assess the efficacy and safety of high-dose pyridoxine treatment for seizures and its effects on development in patients with inherited glycosylphosphatidylinositol deficiencies (IGDs). In this prospective open-label multicenter pilot study, we enrolled patients diagnosed with IGDs using flow cytometry and/or genetic tests. The patients received oral pyridoxine (20–30 mg/kg/day) for 1 year, in addition to previous treatment. All nine enrolled patients (mean age: 66.3 ± 44.3 months) exhibited marked decreases in levels of CD16, a glycosylphosphatidylinositol-anchored protein, on blood granulocytes. The underlying genetic causes of IGDs were PIGO, PIGL, and unknown gene mutations in two, two, and five patients, respectively. Six patients experienced seizures, while all patients presented with developmental delay (mean developmental age: 11.1 ± 8.1 months). Seizure frequencies were markedly (>50%) and drastically (>90%) reduced in three and one patients who experienced seizures, respectively. None of the patients presented with seizure exacerbation. Eight of nine patients exhibited modest improvements in development (P = 0.14). No adverse events were observed except for mild transient diarrhea in one patient. One year of daily high-dose pyridoxine treatment was effective in the treatment of seizures in more than half of our patients with IGDs and modestly improved development in the majority of them. Moreover, such treatment was reasonably safe. These findings indicate that high-dose pyridoxine treatment may be effective against seizures in patients with IGDs, although further studies are required to confirm our findings. (University Hospital Medical Information Network Clinical Trials Registry [UMIN-CTR] number: UMIN000024185.)